Age-Related Deficits of Dual-Task Walking: A Review - Rainer Beurskens; Otmar Bock (Neural Plasticity)
This review summarizes our present knowledge about elderly people's problems with walking. We highlight the plastic changes in the brain that allow a partial compensation of these age-related deficits and discuss the associated costs and limitations. Experimental evidence for the crucial role of executive functions and working memory is presented, leading us to the hypothesis that it is difficult for seniors to coordinate two streams of visual information, one related to navigation through visually defined space, and the other to a visually demanding second task. This hypothesis predicts that interventions aimed at the efficiency of visuovisual coordination in the elderly will ameliorate their deficits in dual-task walking.